Kesukubangsaan dan Negara Kebangsaan di Indonesia: Prospek Budaya Politik Abad ke-21 - H. Andi Mattulada (Antropologi Indonesia, 1999)
In this article the author examines the problem of ethnicity and the Indonesian nation-state. He asserts that Indonesia's history is marked by the tension between the country's ideological basis - as started in the preamble to its constitution- and the structural foundations stipulated in the chapters of that constitution. Working to achieve unity in diversity through the power granted him by the constitution, Soekarno applied the geopolitics based upon the Blut und Boden Theorie. However, each and every ethnic group that was to be united met the criteria of Blut und Boden and others. The concentration of power upon the president, reinforced by the Javanese conception of power, continued with Soeharto; eventually leading to the reform movement wherein in the many smaller groups in the union have begun to speak out. The author concludes that the centralization of power of the past must be replaced by a system with broad regional autonomy. While remaining true to the principle of the constitution, the distribution of economic power among the regions serve also as a safeguard against future crisis.